Eccentric loading on the tibial plate after knee replacement - Abdul Kadir, Mohammed Rafiq; Kamsah, N.; Aziz, Z. (Springer Berlin Heidelberg, 2008)
Osseointegration is vital to the success of total knee arthroplasty. This intimate bone integration however, mostly occured on the femoral component but not on the tibial component. Failure to achieve sufficient primary fixation of the tibial component has been regarded as the major factor affecting bone growth. The problem would be more apparent under eccentric loading which created complex rocking motions in both flexion and extension during gait. Fixation features in terms of protrusion on the undersurface of the tibial component include flange, screws and stem. In this study, the effect of three fixation features under physiological loading was analysed using non-linear contact finite element analysis. Three dimensional model of a human tibia was reconstructed from CT dataset. Three different tibial compartments — the cross-flange, the linear flange and the tapered cylindrical shaft — were modeled without the polymeric tibial insert. The component was then positioned on the tibial plateau and bone preparation was virtually simulated. Each model was then meshed with solid tetrahedrals and material properties were assigned to the bone and the prostheses. Coefficient of friction between the bone and the implant was set to 0.3. Pressure was applied on the medial plateau with magnitude corresponds to an eccentric load of 1250N. Non-linear contact analysis was performed on each of the three components, together with a validated micromotion algorithm to predict instability at the bone-implant interface. Results showed that the cross flange was the most stable under eccentric load with micromotion values did not exceed the threshold limit for osseointegration.